2001
DOI: 10.2307/3558364
|View full text |Cite
|
Sign up to set email alerts
|

Species relationships in Lactuca s.l. (Lactuceae, Asteraceae) inferred from AFLP fingerprints

Abstract: An AFLP data set comprising 95 accessions from 20 species of Lactuca s.l. (sensu lato) and related genera was generated using the primer combinations E35/M48 and E35/M49. In phenetic analyses of a data subset, clustering with UPGMA based on Jaccard's similarity coefficient resulted in the highest cophenetic correlation, and the results were comparable to those of a principal coordinates analysis. In analyses of the total data set, phenetic and cladistic analyses showed similar tree topologies for the well-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 26 publications
9
130
0
1
Order By: Relevance
“…They found that L. sativa and L. serriola shared all alleles at 36% of their loci, and that L. sativa was a complete subset of L. serriola at 67% of its loci. Koopman et al (1998Koopman et al ( , 2001, using ITS (internal transcribed spacer) sequences and AFLPs (amplified fragment length polymorphisms) as markers, confirmed many of the infrageneric boundaries suggested by Feráková (1977), and concluded that L. sativa and L. serriola are conspecific. They considered L. sativa the correct name for both species because of nomenclatural priority.…”
Section: Phylogeny Ofsupporting
confidence: 51%
See 2 more Smart Citations
“…They found that L. sativa and L. serriola shared all alleles at 36% of their loci, and that L. sativa was a complete subset of L. serriola at 67% of its loci. Koopman et al (1998Koopman et al ( , 2001, using ITS (internal transcribed spacer) sequences and AFLPs (amplified fragment length polymorphisms) as markers, confirmed many of the infrageneric boundaries suggested by Feráková (1977), and concluded that L. sativa and L. serriola are conspecific. They considered L. sativa the correct name for both species because of nomenclatural priority.…”
Section: Phylogeny Ofsupporting
confidence: 51%
“…Ryder and Whitaker (1976) summarized the early and recent history of L. sativa, and referred to a sativa-serriola complex that was "large, polymorphic and capable of free interchange of genes with little, if any, reduction in fertility". The origin of cultivated lettuce is still contentious, but recent molecular work supports the view that it originated directly from L. serriola through selection (Kesseli et al 1991;Koopman et al 1998Koopman et al , 2001. Kesseli et al (1991) examined variation in RFLPs (restriction fragment length polymorphisms) in cultivated lettuce accessions and five Lactuca species, and concluded that L. sativa was closely related to L. serriola, but not to L. saligna or L. virosa.…”
Section: Phylogeny Ofmentioning
confidence: 96%
See 1 more Smart Citation
“…Crop lettuce differs from prickly lettuce only for characters connected to domestication, like rapid growth, short life-cycle, absence of dormancy, and generally absence of prickles on the leaves and on the stem (Frietema de Vries et al, 1994). Both species are diploid, and their chromosome length and genetic background are equivalent (Koopman et al, 2001;Lindqvist, 1960a). Selffertility prevails in L. serriola (Mejias, 1994) and is commonly regarded as being complete in L. sativa (Jones, 1927).…”
Section: Introductionmentioning
confidence: 99%
“…The recent information about taxonomy and relationships within the genus Lactuca L. was summarized by KOOPMAN et al (1998), LEBEDA (1998), KOOPMAN (1999) and LEBEDA and ASTLEY (1999), KOOPMAN et al (2001), LEBEDA et al (2001a). Precise taxonomical delimitation and uniform classification of this genus is limited by absence of data on morphology, anatomy, karyology, biochemical and molecular variability (LE-BEDA et al 1999).…”
Section: Taxonomy Of the Genus Lactuca Lmentioning
confidence: 99%